2003
DOI: 10.1063/1.1621621
|View full text |Cite
|
Sign up to set email alerts
|

Detailed dynamics of a complex photochemical reaction: Cis–trans photoisomerization of stilbene

Abstract: Detailed simulations are reported for the dynamics of electrons and nuclei during the cis to trans photoisomerization of stilbene. Our method, which employs a semiclassical description of both the nuclear motion and the radiation field, is described in the text. After excitation of electrons from the HOMO to the LUMO by a femtosecond-scale laser pulse, two principal avoided crossings are observed between the HOMO and LUMO levels, each of which leads to substantial depopulation of the LUMO. Based on our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 34 publications
3
65
0
2
Order By: Relevance
“…The method used here is the so-called semiclassical electron-radiation-ion dynamics to emphasize both its strengths and its limitations [32][33][34][35] . The valence electrons are treated quantum-mechanically, while both the radiation field and the motion of the ion cores are treated classically.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method used here is the so-called semiclassical electron-radiation-ion dynamics to emphasize both its strengths and its limitations [32][33][34][35] . The valence electrons are treated quantum-mechanically, while both the radiation field and the motion of the ion cores are treated classically.…”
Section: Methodsmentioning
confidence: 99%
“…37 The electronic states were calculated with a density-functional-based method 36,38 , which has similar strengths and limitations as TDDFT. Reliability of our simulation method for light-driven molecular dynamics has been calibrated and verified systematically for a series of light-responding molecules [33][34][35]39,40 .…”
mentioning
confidence: 99%
“…Very recently, we have performed a series of simulation studies on the molecular response to ultrashort laser irradiation [9][10][11][12]. These include the photo-isomerization of cis-and trans-butadiene [9,10], and cis-stilbene [11,12] using a semiclassical approach.…”
Section: Introductionmentioning
confidence: 99%
“…These include the photo-isomerization of cis-and trans-butadiene [9,10], and cis-stilbene [11,12] using a semiclassical approach. The simulation results provide insights into the dynamics of these complicated photoreactions.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that cis-stilbene approaches both the (S 0 /S 1 ) coop and (S 0 /S 1 ) pyr CI points. Dou and Allen 61 have performed direct dynamics simulations for cis-stilbene on the S 1 state by using Hamiltonian matrix elements fitted to tightbinding local-density approximation DFT calculations. The authors found two principal avoided crossings along the single trajectory and proposed that the first crossing point leads to DHP formation and the second to the trans-stilbene product.…”
mentioning
confidence: 99%